2023
DOI: 10.21203/rs.3.rs-2443040/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3-dimensional analysis of hard- and soft-tissue symmetry in a Chinese population

Abstract: Background Facial symmetry severely affects appearance and function. Large numbers of patients seek orthodontic treatment to improve facial symmetry. However, the correlation between hard- and soft-tissue symmetry is still unclear. Our aim was to investigate the hard- and soft-tissue symmetry in subjects with different levels of menton deviation and sagittal skeletal classes with 3D digital analysis and to investigate the relationship between the entire and individual hard- and soft-tissues. Methods A total … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Despite the considerable quantity of image acquisition systems presently employed for 3D photography, research use for this type of imaging is limited to a handful of devices, of which 2 are the most extensively utilized. First, we found that the most used system was the 3dMD, 10,[12][13][14][15][16][17][18][19][20][21][22][23][24] which consists of 2 groups of 3 cameras, each located at 45 degrees to the right and left side target, and was used by 52% of the authors, followed by the Vectra M3, [25][26][27][28][29][30][31][32] which consists of a device composed of 3 groups of 2 cameras each and was used by 28% of the authors. In contrast, some other systems were used by some authors.…”
Section: System Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the considerable quantity of image acquisition systems presently employed for 3D photography, research use for this type of imaging is limited to a handful of devices, of which 2 are the most extensively utilized. First, we found that the most used system was the 3dMD, 10,[12][13][14][15][16][17][18][19][20][21][22][23][24] which consists of 2 groups of 3 cameras, each located at 45 degrees to the right and left side target, and was used by 52% of the authors, followed by the Vectra M3, [25][26][27][28][29][30][31][32] which consists of a device composed of 3 groups of 2 cameras each and was used by 28% of the authors. In contrast, some other systems were used by some authors.…”
Section: System Usedmentioning
confidence: 99%
“…Baysal et al (2016) 48 and Dindaroğlu et al (2016) 49 reported that landmarks marked directly on the 3D facial file have higher reproducibility than those previously marked on the face. However, although most authors did not perform this premarking, using direct marking in the 3D files, 10,[13][14][15][16][17]19,21,[23][24][25][26][31][32][33][34][35]37,38,41 a large group of authors made the selection of points with a dermatograph pencil before making the images. 12,[27][28][29][30]36 Of all the articles analyzed, only Cassi et al (2018), 9 Parra and colleagues (2019), Zhou and colleagues (2023), Andrade and colleagues (2017), Wu and colleagues (2022), Bernini and colleagues (2020), Mc-Cormick et al (2021), 2 Godt and colleagues (2013), Baksi et al (2020), 1 and Zhao and colleagues (2023) evaluated the reproducibility of dot-marking, where a similar degree of reproducibility was observed in all studies, regardless of the dotmarking system used.…”
Section: Landmarksmentioning
confidence: 99%